2003
DOI: 10.1111/j.1348-0421.2003.tb03380.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Core Protein Selectively Inhibits Synthesis and Accumulation of p21/Waf1 and Certain Nuclear Proteins

Abstract: By using a vaccinia virus‐T7 expression system, possible effects of hepatitis C virus (HCV) core protein on synthesis and accumulation of host cellular proteins transiently expressed in cultured cells were analyzed. Immunoblot and immunofluorescence analyses revealed that synthesis and accumulation of certain nuclear proteins, such as p21/Waf1, p53, proliferating cell nuclear antigen and c‐Fos, were strongly inhibited by HCV core protein. On the other hand, synthesis and accumulation of cytoplasmic proteins, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 58 publications
0
7
1
2
Order By: Relevance
“…On the other hand, we have noted that expression of NS3 protein was directly related to expressions of p21 and cyclin D1. We have not been able to confirm the in vitro results demonstrating positive [20,21] or negative relationships [22,24] between core protein and p21 protein. We also couldn't demonstrate any correlation between NS5A protein and p21 protein expression [26,27].…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…On the other hand, we have noted that expression of NS3 protein was directly related to expressions of p21 and cyclin D1. We have not been able to confirm the in vitro results demonstrating positive [20,21] or negative relationships [22,24] between core protein and p21 protein. We also couldn't demonstrate any correlation between NS5A protein and p21 protein expression [26,27].…”
Section: Discussioncontrasting
confidence: 65%
“…The cytoplasmic form of core protein augmented p21 expression (via activation of p53) and the mature form in the cell nucleus inhibited it (the p53-independent pathway) [23]. In an another study inhibition of p21 synthesis was demonstrated by the core protein situated in the cytoplasm [24]. Out of the non-structural HCV proteins, NS3 can promote growth [25] but NS5A protein can either promote [26] or inhibit growth via up-regulation of p21 [27].…”
Section: Introductionmentioning
confidence: 97%
“…Immunoblotting was performed as described previously (36). In brief, Huh7-FK2884Gly-1 cells were lysed in a buffer consisting of 50 mM Tris-HCl (pH 8.0), 150 mM NaCl, 0.2% sodium azide, 0.1% sodium dodecyl sulfate (SDS), 0.1% NP-40, and 0.5% sodium deoxycholate.…”
Section: Methodsmentioning
confidence: 99%
“…Controversial observations have been reported about the effects of HCV Core protein on p53 and p21 expressions because of the different subcellular localizations for its nascent or mature forms [19][20][21][22]. Our previous study demonstrated that hnRNP K protein might serve as a p53 coactivator in the non-stress condition [10].…”
Section: The Functional Roles Of Hcv Core Hnrnp K Proteins In the P21mentioning
confidence: 97%